Prophylactic Foley catheter insertion into defunctioning ileostomy to reduce obstruction after colorectal surgery: pilot randomized controlled trial*. Issue 9 (17th May 2020) - Kulasegaran, Suheelan; Li, Ray; Nisbet, Sherry; Vasey, Carolyn; Otutaha, Bacil; Walsh, Michael; Jarvis, John; Moir, Mike H.
Abstract: Background: Defunctioning ileostomies provide faecal diversion in major colorectal surgery. This reduces the consequences of an anastomotic leak. However, the formation of an ileostomy carries risks including obstruction at the level of the fascia. Post‐operative oedema at the level of the fascia may contribute to obstruction. We hypothesize that the prophylactic insertion of a Foley catheter into the afferent limb of a defunctioning loop ileostomy may help decompress and improve time to low‐residue diet (LRD). The objective of the study was to assess the feasibility of a Foley catheter, prophylactically inserted into the afferent limb of a defunctioning loop ileostomy, after major colorectal surgery. Methods: The study was a prospective pilot‐randomized controlled trial. Ethical approval was obtained from Northern B Health and Disability Ethics Committee 15/NTB/91 ANZCTR Trial ID: ACTRN12615000691549. Results: Forty‐nine patients undergoing major elective colorectal surgery with a defunctioning ileostomy, between the years of 2015 and 2018 at North Shore Hospital, Auckland, New Zealand were included in this study. Patients were randomly allocated to either the Foley catheter ( n = 26) or non‐Foley catheter ( n = 23) group. The median time taken to tolerate LRD the primary outcome, was 2 days in the Foley group versus 2 days in the non‐Foley group ( P = 0.05). There were no differences in the secondary outcome measures such as time to stoma output, length of stay or complications. Conclusion: This trial failed to show a statistical difference in time taken to tolerate a LRD residue in the Foley catheter group. There was no difference in length of stay, time to flatus or stoma output. Abstract : This study investigates whether the prophylactic insertion of a Foley catheter into the afferent limb of the defunctioning loop ileostomy reduces post‐operative obstruction at the level of the fascia. Time to tolerating a low‐residue diet was similar between the Foley and no Foley group.